Nurturing tomorrow's antibiotic stewards: An innovative school campaign to combat antimicrobial resistance in Delhi - Sangeeta Sharma; Renu Gupta; Vineeta Bablani; Arti Bahl (Wolters Kluwer Medknow Publications, 2024)
Antimicrobials are lifesaving medicines, but their misuse drives antimicrobial resistance. Schools, as educational hubs wield transformative potential in fostering responsible antimicrobial behavior among students and the broader community. An online campaign targeted Delhi schools, training teachers as master trainers who, in turn, educated 359,940 students. Significant pre- to post-test score improvements were observed among teachers (6.98-8.14; P < 0.01) and students (5.20-6.56; P < 0.01). The campaign received excellent feedback (85%), with 966 students participating in the "IDEAthon" competition. While a single session improved knowledge, continuous engagement and activities are imperative for sustained behavioral change in antibiotic usage.